Isra Mi’raj and the Privilage of Prayer: Study of the Isra Mi’raj Verses in the Qur’an: Isra Mi’raj Dan Keistimewaan Ibadah Shalat: Kajian Terhadap Ayat-Ayat Isra Mi’raj Dalam Al-Qur’an - Aini, Aisyah Nurul; Muna, Arif Chasanul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Background and Objectives: There is a growing tendency among some Muslims to neglect the obligatory five daily prayers, despite their fundamental status and unique virtues. One such virtue is evident in the way the prayer was prescribed during the Isra Mi’raj event, where the Prophet Muhammad (PBUH) received the command directly from Allah. This study aims to clarify the linkage between prayer and Isra Mi’raj, emphasizing how internalizing the event’s implied messages can enhance one’s prayer quality (khushū’). Methodology: This is a qualitative library-based study that analyzes classical and contemporary Islamic sources, especially fiqh-oriented tafsīr, as well as previous research. The collected data were examined thematically to uncover the spiritual dimensions of prayer influenced by the Isra Mi’raj narrative. Main Results: The findings suggest that neglect in performing prayers often stems from a limited understanding of their spiritual significance. By appreciating the extraordinary context of the Isra Mi’raj—where prayer was commanded without an intermediary—believers can deepen their spiritual connection, leading to more focus and humility in performing prayers. Research Contribution: This study provides a conceptual framework linking the Isra Mi’raj narrative to the inner dimensions of prayer. Such insights can serve as a reference in religious education and spiritual development programs, encouraging a view of prayer not as a mere ritual duty but as a profound spiritual encounter. Conclusions: Grasping the meaningful lessons behind Isra Mi’raj enriches the believer’s prayer experience, promoting a consistent, heartfelt, and morally transformative adherence to this core Islamic obligation